DEFORMALISASI TRADISI FIKIH DALAM HUKUM NASIONAL - Muhammad Junaidi (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2014)
A domination of Indonesian citizen around 80% is still lack in the contribution and the role to the Islamic law as the reference of tradition built in the national law. National law tend to apply Duch law tradition based on positivism. Besides, the existence of fiqh is still in the form of analysis without an intention to realize an actualization of the law that can change National law tradition. By using normative Yuridis approach, researcher an discuss comprehensively about the weaknesses and the solution of the law applied in Indonesia. The research result shows the fact, the National law tradition refers to duch law is fail in finding the values sided to the fairness. The contribution from Duch law tradition used continuously through colonialism. Then, the role of fiqh tradition that gives priority on the goodness that have to be able to play it’s role in taking over Duch law tradition in our National law. Then the problem is not our courage to force Fiqh theories in each role of the law.